Stressed states and deformations of the earth's crust of the central part of the Ingul megablock according to the materials of the tectonophysical study of the Novoukrainsky massif - O.B. Gintov; S. V. Mychak (Геофизический журнал, 2011)
The results of the field tectonophysical studies done in the central part of the Ukrainian Shield (USh) in 2005-2009 show that the Novoukrainian massif of the trahite-like granites was formed as a result of the latitudinal crustal extension 2,05 billion years ago during the formation of inter-regional tectonic suture of Kherson-Smolensk. The subsequent crustal deformations that accompanied the formation of the Kirovogradsky, Lelekovsky, Subbotsk-Moshorinsky and other fault zones, as well as the Korsun-Novomirgorod pluton of gabbro-anorthosites and rapakivi-like granites were reflected in the structure of the massif. A detailed study of the Novoukrainian massif and its frame made it possible to establish the chronological sequence of stages and phases of deformation of the central part of the USh from the Archean to the Late Proterozoic.